A scanning tunnelling study of immobilised cytochrome P450cam. - Davis, J; Djuricic, D; Lo, K; Wallace, E; Wong, L; Hill, H (2000)
A site-specifically engineered surface cysteine residue, located in a region where the haem moiety is closest to the surface, is used to anchor cytochrome P450cam enzyme molecules covalently to a gold electrode. More reproducibly ordered adsorption, at high coverage, occurs with this K344C mutant than with the wild-type enzyme. The subsequently formed close-packed monolayer arrays have been probed by scanning tunnelling microscopy under ambient conditions and under aqueous (buffered) solution at high resolution. Initial indications suggest that the immobilised enzyme is both electrochemically addressable and catalytically active.